Testamentary trusts in English Law: an introductory approach - Lafuente Sánchez, Raúl (CUADERNOS DE DERECHO TRANSNACIONAL, 2015)
The trust is a legal institution developed in courts of equity in common law jurisdictions. Among the different types of trusts, the testamentary are created under a will and, traditionally, have been considered as an effective structure when considering estate planning. Nevertheless, this figure has not passed to civil jurisdictions. This article is aimed to offer a general and preliminary analysis of this institution in English law, identifying the parties involved and the formalities required to create a testamentary trust, analysing the purpose for which they are used, and highlighting the main advantages and incentives offered by this instrument. It must be read in the context of the debate about the recognition of trusts in Civil law jurisdictions in order to conclude whether the testamentary trusts may be an appropriate and useful instrument to be used as an estate-planning tool. Key words: Trusts, testamentary trusts, international succession law, English law, settlor, trustee, beneficiaries. Resumen: El trust anglosajón es una creación de los tribunales de equidad en los países del Common Law. Entre los diferentes tipos existentes, los trusts sucesorios son creados por el causante en su testamento y, tradicionalmente, se han considerado muy útiles en la planificación sucesoria. Sin embargo, esta figura no se encuentra regulada en la mayoría de los países de tradición jurídica de Civil Law. Este artículo ofrece un análisis general y preliminar sobre esta institución en Derecho inglés, identificando para ello las partes y los requisitos legales para su constitución, analizando sus objetivos y finalidad, y destacando las principales ventajas e incentivos que ofrece este instrumento. Y debe ser entendido en el marco del debate abierto en torno al reconocimiento de la figura del trust en los países de Civil Law, con el fin de reflexionar sobre la utilidad de los trusts sucesorios en la planificación sucesoria en estos países. Palabras clave: Trust, trusts testamentarios, Derecho sucesorio internacional, Derecho inglés, settlor, trustee, beneficiarios.